Hybrid electrochemical capacitor device testing of various carbon electrodes - Lee, Chang Kwang. (2010)
By combining LiCoO2 half-cell and a carbon compound namely, super P carbon black, activated carbon, SWCNT and MWCNT which are also currently being researched in super capacitors to create a hybrid cell or hybrid electrochemical capacitor. 4 different types of the carbon compound anodes were tested by galvanostatic charging and discharging. Out of the 4 carbon compounds used, results show that anode that used purely Super P carbon black had the highest energy density and specific capacity, while CNT anodes could increase the devices power density however it had low energy density compared to the super P device. We even tried mixing 10% Super P and SWCNT together to create a high energy density and power density device; however we had only discrepancy in the result. Nevertheless this results showed some potential of enhancing the power and energy density of the device storage, when compared with the other single material electrodes. This could be a platform for future investigation of the enhancement of power and energy density of hybrid electrochemical capacitor or charge storage devices in the future.